Recomendaciones a la productividad en Manizales a través de mejores condiciones de empleo (2017)
This document analyzes the productivity of the industrial system of the city of Manizales, Colombia, from a labor market perspective, as a contingency to the phenomenon of structural heterogeneity that presents the productive apparatus, determined by the loss of dynamism of the coffee industry, which defines the relationship urbanization-industrialization under characteristics of dependent trajectory. This causes the city to be limited to develop cluster initiatives that allow the creation of high-quality jobs. In this sense, four public policies, chosen based on the potential boost to the city’s productivity, were compared to finally emerge two industrial bets around biotechnology and ICT, from which Manizales could be renewed and become a nodal city.